THREAT UTTERANCES IN ONLINE LOAN COLLECTION - Muhammad Rifqi Herjoko; Filia Filia (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2023)
This paper examines threat utterances in online loan collection. Online loans are one of the financial services that are currently being used by the public. However, online loan collection efforts have created its own problems among the public. The purpose of this study is to explain threat utterances of online loan collection. Data sources for this research are 42 screenshots of online loan collection on Instagram accounts. This research data is utterance structure of threats when the creditor collects the debtor. This study uses Beller's (2005) theory over types of threatening utterances. Based on the results, the findings of this study are more towards threat utterances constructions of (i) conditional, (ii) conjunctive, and (iii) disjunctive. Threat utterances in the form of conditional used more frequent compared to the other construction.